2017
DOI: 10.1016/j.immuni.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Chromatinscape Suggests Alternative Mechanisms of Glucocorticoid Receptor Action

Abstract: Summary Despite the widespread use of glucocorticoids (GCs), their anti-inflammatory effects are not understood mechanistically. Numerous investigations have examined the effects of glucocorticoid receptor (GR) activation prior to inflammatory challenges. However, clinical situations are emulated by a GC intervention initiated in the midst of rampant inflammatory responses. To characterize the effects of a late GC treatment, we profiled macrophage transcriptional and chromatinscapes with Dexamethasone (Dex) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(141 citation statements)
references
References 51 publications
14
125
1
1
Order By: Relevance
“…Through binding to distal enhancers whose chromatin accessibility is usually cell‐type specific, the glucocorticoid receptor reprogrammes the inflammatory regulome. After LPS‐induced genomic reprogramming, the glucocorticoid receptor produced a similar gene expression to the kind observed before the LPS challenge, while enhancing the expression of metabolic genes . Whereas glucocorticoids suppress the inflammatory regulome, they cause hyperglycaemia, hyperlipidemia, osteoporosis and immunosuppression.…”
Section: Intracellular Therapies That Target Signal Transducers In Prmentioning
confidence: 77%
See 1 more Smart Citation
“…Through binding to distal enhancers whose chromatin accessibility is usually cell‐type specific, the glucocorticoid receptor reprogrammes the inflammatory regulome. After LPS‐induced genomic reprogramming, the glucocorticoid receptor produced a similar gene expression to the kind observed before the LPS challenge, while enhancing the expression of metabolic genes . Whereas glucocorticoids suppress the inflammatory regulome, they cause hyperglycaemia, hyperlipidemia, osteoporosis and immunosuppression.…”
Section: Intracellular Therapies That Target Signal Transducers In Prmentioning
confidence: 77%
“…After LPS-induced genomic reprogramming, the glucocorticoid receptor produced a similar gene expression to the kind observed before the LPS challenge, while enhancing the expression of metabolic genes. 190 Whereas glucocorticoids suppress the inflammatory regulome, they cause hyperglycaemia, hyperlipidemia, osteoporosis and immunosuppression. The untowards side effects of glucocorticoid therapy limit its utility in inflammation-mediated diseases.…”
Section: Classic Anti-inflammatory Agents: Nonsteroidal Anti-inflammentioning
confidence: 99%
“…We next tested if the GR directly regulates the expression of checkpoint receptor genes and IL-10. First, we analyzed GR-binding peaks in the loci of Havcr2 (Tim-3), Pdcd1 (PD-1), Lag3, Tigit, and IL10 in publicly available ChIP-seq data (Oh et al, 2017) from bone marrow-derived macrophages (BMDMs) (Figure S6). We found GR-binding peaks in the loci of Havcr2, Lag3, and IL10 but not Pdcd1 or Tigit, reflecting the lack of PD-1 and Tigit expression in BMDMs.…”
Section: The Glucocorticoid Receptor Transactivates the Expression Ofmentioning
confidence: 99%
“…For instance, Oh et al, showed that activation of GR after LPS treatment caused similar gene repression as activation of GR before LPS treatment, and that DNA occupancy by GR was not predictive of gene expression repression, contradicting the "trans-repression by tethering" model. Rather, GR activation was found to directly induce the expression of inhibitors of NF-κB (and AP-1) and this was proposed to cause genome-wide blockade of NF-κB interaction with chromatin [95]. This suggests that protein tethering leading to DNA-bound monomeric GR trans-repression can only account for a minority of repressive events [96].…”
Section: Gr-binding Site Sequences and Gr-mediated Transrepressionmentioning
confidence: 99%